Habituation Strategy in Forming Student Character at Al-Fajar Islamic High School, Bekasi City - Wamidi Fauza; Akil; Ahcmad Junaedi Sitika (al-Afkar, Journal For Islamic Studies, 2023)
National Education develops skills and forms good national character and civilization in the context of shaping the life of the nation, and seeks to develop opportunities for students to become human beings who believe in and fear God Almighty, have noble character, are healthy, capable, creative and independent and become democratic and responsible citizens regulated by the Law of the Republic of Indonesia No: 20 of 2003 concerning the national education system. To get students with good grades, it is necessary to form a child's personality or character in accordance with social values, starting from the family environment. The problem is, character education requires habituation, what are the strategies for instilling social values, what are the strategies for getting used to them, and what are the supporting and inhibiting factors in the implementation of students' character building strategies. The research approach used in this research is qualitative. Because in this study, researchers examined the activities of several community groups related to behavior change. The results of the study show that as a driving school for Al-Fajar Islamic High School, Bekasi City, it is very conducive to the success of students in both character building and knowledge, which is highly supported by the entire academic community, the students themselves and their parents. learners, and a collaborative environment are important aspects of support. Very effective in applying habituation, forming character with good morals.